2019
DOI: 10.1029/2019gc008433
|View full text |Cite
|
Sign up to set email alerts
|

SKS Splitting Beneath Mount St. Helens: Constraints on Subslab Mantle Entrainment

Abstract: Observations of seismic anisotropy can provide direct constraints on the character of mantle flow in subduction zones, critical for our broader understanding of subduction dynamics. Here we present over 750 new SKS splitting measurements in the vicinity of Mount St. Helens in the Cascadia subduction zone using a combination of stations from the iMUSH broadband array and Cascades Volcano Observatory network. This provides the highest density of splitting measurements yet available in Cascadia, acting as a focus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 95 publications
1
15
0
Order By: Relevance
“…8a) which coincides with the theoretical 'null' direction for the two-layer case (Silver and Savage 1994). Our observed jump in ϕ (SC method) of around π/2 appears to be larger than the synthetic error or jump for a one-layer anisotropy model proposed by Eakin et al (2019) (Fig. 7).…”
Section: ° Binssupporting
confidence: 84%
See 1 more Smart Citation
“…8a) which coincides with the theoretical 'null' direction for the two-layer case (Silver and Savage 1994). Our observed jump in ϕ (SC method) of around π/2 appears to be larger than the synthetic error or jump for a one-layer anisotropy model proposed by Eakin et al (2019) (Fig. 7).…”
Section: ° Binssupporting
confidence: 84%
“…A crucial point is that ϕ values have 45° slopes over backazimuth and a jump when the backazimuth coincides with the null direction. Eakin et al (2019) proposed that for real data with a more realistic SNR of 5-10 also the SC method tends to show such a behavior. Silver and Savage (1994) showed that also for two-layer anisotropy, a jump in ϕ can appear for the SC method.…”
Section: Modeling Results and Interpretationmentioning
confidence: 99%
“…The pair with the maximum correlation represents the fast direction and delay time of the split. One limitation of this method is a systematic misorientation of 45 °at near-null directions; this can be accounted for with modeling of the splitting parameters, detailed in Section 3.3 (Wüstefeld and Bokelmann, 2007;Eakin et al, 2019). To check for the quality of splits, we also calculate splitting parameters using the minimum energy and eigenvalue methods (Silver and Chan, 1991).…”
Section: Shear Wave Splittingmentioning
confidence: 99%
“…Even if the slab supplies some modest amount of water beneath the CSZ, it might not directly influence the upper mantle below our study area, given that the slab at this position is located within the transition zone (Figure 2). We propose that material influx from the subslab mantle (Figure 8), which is likely dominated by subslab entrainment (Eakin et al, 2019) and anticipated to be relatively hydrated, toward the mantle above the slab in the back-arc might explain the moderately high water contents. A combination of poloidal and toroidal flow in the CSZ system, suggested by several authors (e.g., Long, 2016;Zandt & Humphreys, 2008;Zhou et al, 2018;Zhu et al, 2020), may play a role in transporting and distributing subslab mantle into the back-arc.…”
Section: Water Content Of the Asthenospherementioning
confidence: 93%